Asociación entre calidad de sueño y Síndrome de Intestino Irritable en estudiantes de Medicina Humana. - Torres Chiclayo, Sofia Dayli (2023)
To determine the association between sleep quality and Irritable Bowel Syndrome in medical students during the period from July 2021 to January 2022. Material and Methods: A cross-sectional analytical design was carried out; A survey was applied to medical students of the Antenor Orrego Private University of the ninth - twelfth semester, during July 2021 until January 2022; During this period of time, 199 surveys were collected, of which 177 met the inclusion criteria. Pearson's Chi Square test was used to determine if there is an association between both variables. Results: Of the 177 students, 34 of them had Irritable Bowel Syndrome (IBS), of these, 32 are the ones with poor sleep quality and 2 with good sleep quality; In contrast, 143 were the students who did not have IBS, 18 were the ones with good sleep quality, and 125 poor sleep quality. According to the Chi square test, there was no significant association between sleep quality and Irritable Bowel Syndrome (p>0.05). Conclusions: There is no association between sleep quality and irritable bowel syndrome in Human Medicine students.